Coiling Using Dual Microcatheter Technique—A Novel Approach - Arvind Kumar; Swarup Sohan Gandhi; Ashok Gandhi; Trilochan Srivastav; Devendra Purohit (Indian Journal of Neurosurgery, 2022)
Posterior circulation aneurysms are difficult to treat, and if an incorporated artery is arising from the neck of aneurysm, management becomes much more challenging. Here, we are describing a novel technique used to treat a patient with a large, wide-necked left vertebral artery (VA)-posterior inferior cerebellar artery (PICA) junctional aneurysm. PICA seems to be arising from the aneurysm neck, but the aneurysm neck was not very clearly defined. So, we placed a second microcatheter into PICA, which not only allowed the coils to be placed in the aneurysm, without disrupting the flow through PICA but also helpful in assessing the aneurysmal occlusion. This technique allowed coils to be placed successfully without compromising flow through PICA.